Targeting vascular normalization: a promising strategy to improve immune–vascular crosstalk in cancer immunotherapy - Qian, Cheng; Liu, Chaoqun; Liu, Weiwei; Zhou, Rui; Zhao, Liang (Frontiers in Immunology, 2023)
Blood vessels are a key target for cancer therapy. Compared with the healthy vasculature, tumor blood vessels are extremely immature, highly permeable, and deficient in pericytes. The aberrantly vascularized tumor microenvironment is characterized by hypoxia, low pH, high interstitial pressure, and immunosuppression. The efficacy of chemotherapy, radiotherapy, and immunotherapy is affected by abnormal blood vessels. Some anti-angiogenic drugs show vascular normalization effects in addition to targeting angiogenesis. Reversing the abnormal state of blood vessels creates a normal microenvironment, essential for various cancer treatments, specifically immunotherapy. In addition, immune cells and molecules are involved in the regulation of angiogenesis. Therefore, combining vascular normalization with immunotherapy may increase the efficacy of immunotherapy and reduce the risk of adverse reactions. In this review, we discussed the structure, function, and formation of abnormal vessels. In addition, we elaborated on the role of the immunosuppressive microenvironment in the formation of abnormal vessels. Finally, we described the clinical challenges associated with the combination of immunotherapy with vascular normalization, and highlighted future research directions in this therapeutic area.